Formation of a Generation of Moderate Santri through Strengthening the Values ​​of Religious Moderation in Islamic Boarding Schools - Qohar, Abd.; Hidayat, Eko; Faizal, Liky; Mukri, Moh. (Analisis: Jurnal Studi Keislaman, 2025)
Strengthening religious moderation is a strategic issue in Islamic boarding school education amidst the increasing challenges of exclusive and extreme religiosity. Islamic boarding schools play a crucial role in instilling balanced, just, and tolerant Islamic values ​​through distinctive educational traditions. Therefore, fostering moderate religious values ​​as a central focus in religious life is crucial, especially for the younger generation living in a heterogeneous society. This study employed a qualitative approach with a descriptive-analytical approach. The research locations included An-Noor and An-Nahl Islamic Boarding Schools in Bandar Lampung. Data collection was conducted through observation, in-depth interviews, and documentation studies. Data analysis included data reduction, data presentation, and conclusion drawing. The results indicate that strengthening religious moderation effectively occurs through a holistic, integrative, and experience-based pedagogical process. The values ​​of tawassuṭ, tawāzun, tasāmuḥ, and al-‘adl are internalized through dialogic learning, the exemplary behavior of kiai and ustaz, and the daily culture of students. Religious moderation is not positioned as an external ideology, but rather as an actualization of classical Islamic values ​​that have theological legitimacy in the concept of ummatan wasaṭan and the principle of justice in the Qur'an. The integration of cognitive, affective, and practical approaches encourages the transformation of students' character toward a reflective, inclusive, and socially responsible religious attitude.